Liberation technology in El Salvador : re-appropriating social media among alternative media projects - Harlow, Summer (Palgrave Macmillan, 2020)
1. Introduction -- 2. The Roots of El Salvador's Alternative and Digital Media Environment -- 3. Diario CoLatino -- 4. Radio Victoria -- 5. Voces -- 6. Política Stereo -- 7. Common Threads: A Comparative Analysis -- 8. Conclusions: Toward an understanding of participation in and through technology.